Analytical Solution for Composite Foundation with Permeable Pipe Piles Under Uniform Opening Based on Modified Equal Strain Assumption - Weitao YANG; Zheng CHEN; Yaru DUAN; Guoxiong MEI (工程科学与技术)
Composite foundation is an effective technology for treating soft ground and is widely used in engineering practices. Permeable pipe piles combine the advantages of the permeability of granular piles with the high bearing capacity of adhesive columns, offering a new option for foundation reinforcement. The soil consolidation differential equations and definite solution conditions are established based on the modified equal strain assumption to explore the consolidation characteristics of a composite foundation treated by permeable pipe piles under external loads. This assumption considers the penetration depth of the pile into the cushion and underlying layer, where the permeable pipe pile-soil interface is regarded as an impeded boundary. Various forms of surcharge stress distribution and the disturbance effect are also considered. Then, the finite sine Fourier transform derives analytical solutions for the excess pore-water pressure in the soil element, settlement, and consolidation degree of the composite foundation. The validity of these solutions is confirmed by comparison to the degenerate case, and numerical solutions are calculated using the finite difference technique. Finally, the influences of factors such as the opening ratio, opening radius, distribution form of surcharge stress in the foundation, disturbance effect, and the compression modulus of the cushion and underlying layer on the consolidation characteristics of the composite foundation are investigated through parametric analyses. Compared to conventional pipe piles, the results showed that permeable pipe piles significantly accelerate the dissipation of excess pore-water pressure in the soil around the piles; the higher the opening ratio and the smaller the opening radius, the quicker the dissipation occurs. The fastest consolidation rate occurs when the surcharge stress is distributed in an inverted triangle, and the disturbance effect is not considered. In addition, the consolidation rate of the foundation increases with the increment of the compression modulus of the cushion and underlying layer. The results of this research can provide a theoretical basis for the advancement and engineering design of permeable pipe pile technology.